Anti-Sars-CoV-2 vaccination campaign in children aged 5-11 years: the experience of a mass vaccination center in the city of Milan - Astorri, Elisa; Mazziotta, Francesco; Macrelli, Claudio; Tiwana, Navpreet; Letzgus, Matteo; Bisesti, Alberto; Laquintana, Dario; Chiappa, Laura; Piatti, Alessandra; Sottocorno, Marcello; Falbo, Francesco; Rosso, Matilde; et al. (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: After the approval of the anti-Sars-CoV-2 vaccines for the pediatric population, it is necessary to encourage the immunization of children aged 5-11 years, as this can reduce intergenerational transmission. Therefore, this goal has become a priority for the COVID 19 vaccination campaign in Italy. In the city of Milan, the mass vaccination center (MVC) Fiera Milano City, previously settled for general population, became the main site to host pediatric vaccinations. The center was consequently remodeled to ensure a suitable space for children. This paper provides an overview on the organization strategy implemented by Fondazione IRCCS Ca’ Granda Ospedale Maggiore Policlinico. The modular structure and the wide surface available in the center allowed the administration of hundreds of vaccines per day, especially in the first opening phase.Methods: All the data for the entire period of activity of Fiera MCV, from December 16th 2021 to February 20th 2022, were analyzed using descriptive statistics.Results: During the entire period of activity, from 16 December 2021 to 20 February 2022, 23% of the population in the province of Milan aged 5-11 years has been reached and vaccinated with at least one shot of vaccine in this center.Conclusions: Despite an enthusiastic response in the first weeks of the campaign, a progressive reduction in vaccination adherence was observed, maybe due to the absence of restrictive measures for unvaccinated children in Italy.